(untitled) - Russell, Bertrand (London, 1965)
This book contains the first haft of a book called Freedom & Organization, 181401914, published in 1934. The second half of this book will be reprinted under the title, "Freedom versus organization, 1776-1914".
Keywords: Châu Âu,Europe; Chính trị và chính phủ,Politics and government; 1789-1900,1789-1900